Design an automatic curtain using LDR / Mohd Yassir Ali and Nur Hazahsha Shamsudin - Ali, Mohd Yassir; Shamsudin, Nur Hazahsha (2005)
In this semester, faculty of Electrical Engineering Mara University of Technology was describing to their students to make a “Smart Home” for final project. Smart home is house that will give much benefit to us. There are many devices that we must use for completing one smart home such as automatic curtain for window, alarm sensor, heat sensor and etc. In this Smart Home project we choose to build automatic curtain for window as one device to completing one Smart Home. “Design an automatic curtain using LDR” is our name project. This project has been design to close and open the curtain at the window with automatically depends on the light and dark. The dark on relay circuit has been using in this project as an automatic controller to close and open the curtain. When dark level is low or light situation the curtain at the window will be open automatically. However, when dark is high or dark situation the curtain will be close automatically. The advantages of the automatic curtain for window are making our life easier. Every house should use this device because it made our house more comfortable and smart. Almost house at the foreign country such as Europe and Japan use this controller for make their life comfortable and easier either they staying at a house or leaving their house.